Perioperative anaesthetic management of a child with cushings syndrome for bilateral adrenalectomy (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Nearly twenty five percent of the cases of cushings syndrome are due to adrenal hyperplasia without an ACTH secreting tumour. Twenty percent of patients with endogenous cushing have adrenocortical tumour about half of which are benign adenoma. Surgical intervention done due to failed medi cal therapy and in case of adrenal adenoma. A child aged 4½ years, weighting 29kg with features suggestive of cushings syndrome was admitted under paediatric surgery unit in Bangabandhu Sheikh Mujib Medical University. On investigation serum cortisol levels were raised. blood pressure was controlled by ACE inhibitor, calcium channel blocker and beta-blocker. He was scheduled for resection of adrenal cortical tumour. Electrolyte imbalance was corrected, steroid replacement was done. Patient was haemodynamically stable preoperatively.Surgery was completed unevenetfuly. Postoperatively patient was kept in ICU, ventilation maintained by control mode (CMV). After 24 hours the patient was extubated. When the patient found haemodynamically stable he was sent to the recovery room. DOI: http://dx.doi.org/10.3329/jbsa.v22i2.18148 Journal of BSA, 2009; 22(2): 84-87